(untitled) (Ingeniería, Sostenibilidad y Sociedad, 2023)
This document reflects the process of ideation and the proposal of "AKUA - Take care of life", a company that focuses on the generation of kits for the use of rainwater, with the addition of the engineering service in areas of high-water demand, where because of high rains, droughts, contamination of water sources such as water shortages, there is no adequate access and where this resource is wasted significantly. The project is located in the city of Cucuta, Norte de Santander, in its downtown area and it is projected to have coverage for the entire municipality and its metropolitan area, expanding over time at a national and international level.